Murder in the afternoon [large type] - Brody, Frances (Brody, Frances. Kate Shackleton mystery., 2014)
Young Harriet and her brother Austin have always been scared of the quarry where their father works. So when they find him dead on the cold ground, they rush off quickly for help. When help arrives, however, the quarry is deserted and the body is gone. Were they mistaken? It seems like another unusual case for Kate Shackleton -- and Mary Jane, the children's mother, is adamant that only she can help. But Mary Jane is hiding something . . .